2013
DOI: 10.1063/1.4788916
|View full text |Cite
|
Sign up to set email alerts
|

Charge transfer in Sr Zintl template on Si(001)

Abstract: The formation of the half monolayer (ML) Sr Zintl template layer on Si(001) is investigated in a combined experimental and theoretical work consisting of in situ reflection high energy electron diffraction, in situ x-ray photoelectron spectroscopy (XPS), and density functional theory. Starting with clean 2 × 1 reconstructed Si(001), we demonstrate that Sr deposition leads to a charge transfer from the metal to the Si substrate resulting in the disappearance of the asymmetry of Si dimers—an essential structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 47 publications
(61 reference statements)
1
12
0
Order By: Relevance
“…Also, similar series of Sr- and Ba-induced structures can be observed by deposition of appropriate submonolayer amounts of metal atoms at RT, followed by annealing at 530–600 °C. In general, these results are in good agreement with previous studies (refs , , , and ).…”
Section: Experimental Methodssupporting
confidence: 94%
See 1 more Smart Citation
“…Also, similar series of Sr- and Ba-induced structures can be observed by deposition of appropriate submonolayer amounts of metal atoms at RT, followed by annealing at 530–600 °C. In general, these results are in good agreement with previous studies (refs , , , and ).…”
Section: Experimental Methodssupporting
confidence: 94%
“…The Sr coverage of these surfaces was measured to be 0.12 ± 0.03 and 0.19 ± 0.04 ML, respectively. Finally, Choi et al observed the (2 × 3)-Sr reconstruction between 1/6 and 1/4 ML …”
Section: Introductionmentioning
confidence: 96%
“…24 The reconstructed surface in completion of charge transfer has stoichiometry of SrSi 2 , which is the same as that of a bulk SrSi 2 Zintl-Klemm intermetallic compound. 30 We have shown that the ionization energy of the system decreases as a function of Sr coverage, indicating a charge transfer from Sr to Si(001). A large difference in the electronegativity in the system drives charge transfer from A to X, leading to an unusual Zintl phase where the element X assumes the chemical identity of the element to its right in the periodic table.…”
Section: Introductionmentioning
confidence: 81%
“…[6][7][8][9]21,22 The half-monolayer Sr/Si(001) template has been extensively explored both experimentally and theoretically. [23][24][25][26][27][28][29][30] On unreconstructed Si(001), each surface atom has two dangling bonds with two electrons. 31 The second nearest neighbor atoms form a strong r-bond, leading to a 2 Â 1 symmetric dimer structure.…”
Section: Introductionmentioning
confidence: 99%
“…The submonolayer Sr films have been extensively studied both theoretically [7][8][9] and experimentally by several techniques [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%